2006
DOI: 10.1261/rna.2101906
|View full text |Cite
|
Sign up to set email alerts
|

The bunyavirus nucleocapsid protein is an RNA chaperone: Possible roles in viral RNA panhandle formation and genome replication

Abstract: Cellular RNA chaperones are crucial for the genesis of correctly folded functional RNAs. Using several complementary in vitro assays we find that the bunyavirus nucleocapsid protein (N) is an RNA chaperone. In the Bunyaviridae genomic RNA is in stable ''panhandle'' formation that arises through the hydrogen bonding of the terminal nucleotides of the RNA. The RNA chaperone function of N facilitates panhandle formation even though the termini are separated by >2 kb. RNA panhandle formation is likely driven by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…Using this approach, we found that a 50-nt truncation in the ScRNA 3ЈNCR impeded efficient 3Ј-5Ј base pairing. This prediction is in accordance with previous reports for other hantaviruses; a 42-nt truncation in the SgRNA 3ЈNCR of the Sin Nombre virus, for instance, hinders panhandle formation (30). Although the degree of ANDV SmRNA truncation is unknown and we cannot ascertain from currently published information whether a 50-nt truncation truly corresponds to the SmRNA 3ЈUTR, we took the view that the 3ЈNCR featuring the 50-nt truncation (herein named 3ЈUTR) better represents the viral SmRNA 3ЈUTR than the full ScRNA 3ЈNCR.…”
Section: Vol 84 2010supporting
confidence: 93%
“…Using this approach, we found that a 50-nt truncation in the ScRNA 3ЈNCR impeded efficient 3Ј-5Ј base pairing. This prediction is in accordance with previous reports for other hantaviruses; a 42-nt truncation in the SgRNA 3ЈNCR of the Sin Nombre virus, for instance, hinders panhandle formation (30). Although the degree of ANDV SmRNA truncation is unknown and we cannot ascertain from currently published information whether a 50-nt truncation truly corresponds to the SmRNA 3ЈUTR, we took the view that the 3ЈNCR featuring the 50-nt truncation (herein named 3ЈUTR) better represents the viral SmRNA 3ЈUTR than the full ScRNA 3ЈNCR.…”
Section: Vol 84 2010supporting
confidence: 93%
“…Our previous studies demonstrated that after specific recognition, N unwinds the panhandle and remains attached with the 5Ј terminus leaving the 3Ј terminus single stranded. This renders the 3Ј terminus accessible for both annealing of the primer and transcription initiation by the RdRp (15). In the current model (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The characteristic feature of the hantaviral genome is the partially complementary sequence at the 5Ј and 3Ј termini of each of the three genome segments that undergo base pairing and form panhandle structures (4 -6). N is a multifunctional protein playing a vital role in multiple processes of virus replication cycle and has been found to undergo trimerization both in vivo and in vitro (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). During encapsidation, the three viral RNA (vRNA) molecules are specifically recognized by N inside the host cell and targeted for packaging.…”
mentioning
confidence: 99%
“…N is a member of a class of proteins designated as, "RNA chaperones". 10 Since these peptides transiently dissociate higher order RNA structure, 11 the intrinsic chaperone activity of N is likely to substitute for the helicase activity of eIF4A.…”
Section: Bunyavirus N Protein Is a Translation Initiation Factormentioning
confidence: 99%
“…(B) N dissociates the terminal viral RNA panhandle and remains associated with the 5' end of the viral RNA. 10 Dissociation facilitates access of the 3' end of the template for transcription initiation. The capped oligonucleotide acquired by N, is used for transcription initiation and elongation by the polymerase.…”
Section: Role Of N In Translation and Cap-snatchingmentioning
confidence: 99%